Echocardiographic assessment and new advances of right ventricle function in rats with pulmonary hypertension - Wang, Weijie; Ren, Ming; Lu, Dianxiang (Frontiers in Pharmacology, 2025)
Pulmonary Hypertension (PH) is a pathophysiological disease characterized by abnormally elevated pulmonary artery pressures due to a variety of known or unknown causes, which may ultimately lead to right ventricle (RV) failure or even death. The rat has become a major animal model of PH study because of its low cost, genetic control, and similarity of pathologic features to humans. The assessment of right heart function is crucial for basic research on PH and the diagnosis/treatment of PH diseases. Ultrasound imaging has become one of the main methods for assessing right heart function because of its noninvasive measurement, its ability to dynamically monitor the morphology and function of the rat heart, and its low cost and ease of use. Moreover, the new ultrasound technology of speckle tracking is able to detect myocardial dysfunction earlier and more sensitively, and three-dimensional ultrasound generates three-dimensional images of the heart, which is able to more accurately assess the morphology and functional changes of the right heart. In addition, correlation analysis of ultrasound indexes with the gold standard found that pulmonary acceleration time (PAT), PAT/pulmonary ejection time (PET) measured by ultrasound with pulmonary artery systolic pressure (PASP) measured by right heart catheterization (RHC); PAT measured by ultrasound with mean pulmonary artery pressure (mPAP) by RHC; and right ventricular free wall thickness (RVFWT) measured by ultrasound with Fulton’s index, showed good correlation. In this paper, we reviewed the pathologic changes of the heart in PH, the modeling methods of PH rat model, ultrasound imaging for the assessment of right heart function and the advantages of speckle tracking and three-dimensional ultrasound as emerging ultrasound technologies. And we also proposed that the multimodal fusion of ultrasound and cardiac magnetic resonance (CMR), micro computed tomography (micro-CT), artificial intelligence (AI) could be the future direction of cardiac function assessment in PH rat. Accurate assessment of right ventricular function is crucial for further research into the molecular mechanisms of PH and drug screening.